Forgotten fishes: What is the future for small threatened freshwater fish? Population risk assessment for southern pygmy perch, Nannoperca australis. Issue 6 (29th August 2017) - Todd, Charles R.; Koehn, John D.; Pearce, Luke; Dodd, Lauren; Humphries, Paul; Morrongiello, John R.
Abstract: Fish species that have no commercial or recreational value are often overlooked in conservation management, despite serious threats to their long‐term future. This can be termed the 'small threatened freshwater fishes' paradigm. Population viability analysis (PVA) is a useful technique to assess threatened species and conservation management options. While the development and use of population models and population viability analysis is common in conservation, and often used for larger fishes, this has not been so for small threatened freshwater species. This study uses the PVA process to develop a stochastic population model for Nannoperca australis (southern pygmy perch) in temperate south‐eastern Australia. The model was most sensitive to early life‐history survival rates, for which there were no estimates from field data, compared with other model uncertainty. This study also found that the oldest age class had the highest reproductive value, providing unique support to the value of big, old, fat and fecund fish (BOFFFs) in sustaining natural populations. Modelling indicated that a population in stable habitat supporting about 2000 female adults would likely to be viable, able to withstand some disturbance and possibly be used as a source population for reintroductions. In reality, however, there are few populations in the wild of sufficient size to withstand such take for translocations and hence the production of fish through hatchery means may be required. This type of approach should prove useful for the conservation management of many similar species globally.